Internal medicine fellowship directors' perspectives on the quality and utility of letters conforming to residency program director letter of recommendation guidelines. Issue 4 (4th July 2018) - O'Connor, AB; Williams, CM; Dalal, B; Sulistio, MS; Roth, TK; Milne, CK; Collichio, FA; Muchmore, EA; Alweis, R.
ABSTRACT: Background : In May 2017, the Alliance for Academic Internal Medicine (AAIM) published guidelines intending to standardize and improve internal medicine residency program director (PD) letters of recommendation (LORs) for fellowship applicants. Objectives : This study aimed to examine fellowship PDs impressions of the new guidelines, letter writers' adherence to the guidelines, and the impact of LORs that conformed to guidelines compared to non-standardized letters. Methods : The authors anonymously surveyed fellowship PDs from January to March 2018 to gather input about LORs submitted to their programs during the 2017 fellowship application cycle. Results : A total of 78% of survey respondents were satisfied with letters that followed the AAIM guidelines, whereas 48% of respondents were satisfied with letters that did not. Fellowship PDs felt that letters that followed the AAIM guidelines were more helpful than letters that did not, especially for differentiating between applicants from the same institution and for understanding residents' performance across the six core competency domains. Fellowship PDs provided several suggestions for residency PDs to make the LORs even more helpful. Conclusion : Fellowship PD respondents indicated that LORs that followed the new AAIM guidelines were more helpful than letters that did not.